MG53, A Tissue Repair Protein with Broad Applications in Regenerative Medicine - Zhongguang Li; Liyang Wang; Huimin Yue; Bryan A. Whitson; Erin Haggard; Xuehong Xu; Jianjie Ma (Cells, 2021)
Under natural conditions, injured cells can be repaired rapidly through inherent biological processes. However, in the case of diabetes, cardiovascular disease, muscular dystrophy, and other degenerative conditions, the natural repair process is impaired. Repair of injury to the cell membrane is an important aspect of physiology. Inadequate membrane repair function is implicated in the pathophysiology of many human disorders. Recent studies show that Mitsugumin 53 (MG53), a TRIM family protein, plays a key role in repairing cell membrane damage and facilitating tissue regeneration. Clarifying the role of MG53 and its molecular mechanism are important for the application of MG53 in regenerative medicine. In this review, we analyze current research dissecting MG53′s function in cell membrane repair and tissue regeneration, and highlight the development of recombinant human MG53 protein as a potential therapeutic agent to repair multiple-organ injuries.